Discovery of a second geophilomorph species (Myriapoda: Chilopoda) having twenty-seven leg-bearing segments, the lowest number recorded up to the present in the centipede order geophilomorpha - Pereira, Luis Alberto (2013)
Schendylops ramirezi sp. nov. (Myriapoda: Chilopoda), a tiny schendylid centipede (from Rio de Janeiro State, Brazil), is hereby described and illustrated based on the female holotype, male and female paratypes, and additional non-type specimens. This discovery represents the second geophilomorph species characterized by having twenty-seven leg-bearing segments, the lowest number recorded up to the present in the chilopod order Geophilomorpha. So far, this number of pairs of legs (27) had only been found in a single (male) specimen of Schendylops oligopus (Pereira, Minelli & Barbieri, 1995), collected in the vicinity of Manaus, Central Amazon (Brazil). New distribution records for S. oligopus (with which the new species is herein compared in detail), together with complementary descriptive notes and new illustrations are also given. Undiluted 2-Phenoxyethanol (CAS No. 122-99-6) has been used as an effective clearing agent and mounting medium for the preparation of temporary mounts of the examined specimens.